Basic physiology for anaesthetists - Chambers, David; Huang, Christopher; Matthews, Gareth (Cambridge : Cambridge University Press, 2015)
Every trainee in anaesthesia requires a thorough understanding of basic physiology and its application to clinical practice. This comprehensively illustrated textbook bridges the gap between medical school and reference scientific texts. It covers the physiology requirements of the Primary FRCA examination syllabus. Chapters are organised by organ system, with particular emphasis given to the respiratory, cardiovascular and nervous systems. The practical question-and-answer format helps the reader prepare for the oral examination, while'clinical relevance' boxes translate the physiological concepts to clinical practice. The authors include two medical physiologists and a Specialty Registrar in anaesthesia, and thereby bring a unique blend of expertise. This ensures that the book is up-to-date, accessible, and pitched appropriately for the trainee anaesthetist. Packed with easily understood, up-to-date and clinically relevant material, this convenient volume provides an essential'one-stop' resource in physiology for junior anaesthetists.
Title from publisher's bibliographic system (viewed on 13 May 2016).
Keywords: Physiological Phenomena